Assessing Individual Level Predictors of Intermediate Outcomes in a Misdemeanor Diversion Drug Court - Hartsell, Elizabeth N. (American journal of criminal justice, 2024)
We sought to understand the individual level predictors of intermediate outcomes in a diversion drug court. Outcomes included acceptance to drug court, sanction(s), incentives(s), drug test results, and graduation. Because much of the prior literature on individual level predictors of these outcomes is mixed, drug courts can benefit from analysis of their own data to understand what factors are important, or not, for their population. We analyzed administrative data and found significant predictors varied by outcome. Results showed that the court adhered to best practices (Florida Adult Drug Court Best Practice Standards, 2017), because there were no race or sex differences between those accepted to drug court or not, those sanctioned when in drug court, and those graduated successfully versus unsuccessfully discharged. The court team can use these findings to better understand their population, their program, and ensure compliance with best practices. Results also contribute to the broader drug court literature.